2020
DOI: 10.3390/genes11060602
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation Genetic Testing for Chromosomal Abnormalities: Aneuploidy, Mosaicism, and Structural Rearrangements

Abstract: There is a high incidence of chromosomal abnormalities in early human embryos, whether they are generated by natural conception or by assisted reproductive technologies (ART). Cells with chromosomal copy number deviations or chromosome structural rearrangements can compromise the viability of embryos; much of the naturally low human fecundity as well as low success rates of ART can be ascribed to these cytogenetic defects. Chromosomal anomalies are also responsible for a large proportion of miscarriages and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 230 publications
(377 reference statements)
0
95
0
1
Order By: Relevance
“…Preimplantation genetic testing for aneuploidy (PGT-A) is a proven intervention in the treatment of infertility, with decreased clinical miscarriage risk, increased delivery rates from the first embryo transfer attempt, and reduced risk of multiple gestation without compromising success rates. [1][2][3][4][5] 5 However, the diagnostic predictive value of PGT-A, when considering embryonic mosaicism, [6][7][8] or segmental imbalance 9,10 remains controversial and has involved considerable resources to investigate. mosaic range) and 30% to 70% (2.3-2.7 mosaic range).…”
Section: Introductionmentioning
confidence: 99%
“…Preimplantation genetic testing for aneuploidy (PGT-A) is a proven intervention in the treatment of infertility, with decreased clinical miscarriage risk, increased delivery rates from the first embryo transfer attempt, and reduced risk of multiple gestation without compromising success rates. [1][2][3][4][5] 5 However, the diagnostic predictive value of PGT-A, when considering embryonic mosaicism, [6][7][8] or segmental imbalance 9,10 remains controversial and has involved considerable resources to investigate. mosaic range) and 30% to 70% (2.3-2.7 mosaic range).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these studies showed a direct correlation of mosaicism with maternal age [3]. According to the latest estimates, the level of mosaic karyotypes in human preimplantation embryos is significantly lower-from 4% to 22% [20]. The effect of maternal age on the frequency of mosaic embryos is also controversial, since it has not been confirmed in other studies [25,26].…”
Section: Incidence Of Aneuploidy In Ontogenesismentioning
confidence: 97%
“…Approximately half of human preimplantation embryos have aneuploidy, mostly of maternal origin. In addition, the cleavage stage is characterized by mitotic errors that lead to the appearance of mosaic karyotypes [20]. Early studies showed that the frequency of blastocysts with chromosomal mosaicism varied from 17.6% to 95% [3,[21][22][23][24].…”
Section: Incidence Of Aneuploidy In Ontogenesismentioning
confidence: 99%
“…Ethical approval for this project was obtained through the IRB of the Zouves Foundation for Reproductive Medicine (OHRP IRB00011505). For the RNA-seq experiment, embryos were of various ethnic backgrounds and comprised a mix of euploid and aneuploid samples based on evaluation by pre-implantation genetic testing for aneuploidy (PGT-A) 18 (Suppl. Table 1).…”
Section: Human Embryosmentioning
confidence: 99%